Wound Healing Potent of Lyophilized-Secretome Gel from Human Wharton’s Jelly Mesenchymal Stem Cells - Widowati, Wahyu; Faried, Ahmad; Gunanegara, Rimonta Febby; Rahardja, Fanny; Zahiroh, Fadhilah Haifa; Sutendi, Annisa Firdaus; Nindya, Faradhina Salfa; Azis, Rizal; Ekajaya, Renandy Kristianlie; Hadiprasetyo, Dhanar Septyawan (Trends in Sciences, 2024)
Wounds that become infected can lead to serious illness or even death if left untreated. Unfortunately, current wound healing treatments don’t always work well. Achieving optimal wound healing involves the coordination of diverse cellular events facilitated by numerous growth factors, cytokines, and chemokines. One potential solution for addressing the wound healing process is using lyophilized-secretome gel from human Wharton’s Jelly Mesenchymal Stem Cells (hWJMSCs-Sec). This gel, called lyophilized-hWJMSCs-Sec gel (LSG) is created by mixing carbomer gel with hWJMSCs-Sec, then freeze-dry it into a powder to maintain its quality and stability. The quality testing of the topical gel formulation is conducted by measuring. The gel is tested for pH, viscosity, consistency, and its appearance. It’s also tested for antioxidant activity using 2,2-Diphenyl-1-picrylhydrazyl (DPPH), and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays were employed to identify the antioxidant activities of the lyophilized-gel. Proteins level of Tissue Inhibitor of Metalloproteinases-2 (TIMP-2), Epidermal Growth Factor (EGF), basic Fibroblast Growth Factor (bFGF), Interleukin-6 (IL-6), and IL-4 were also measured with the ELISA method. The LSG has a soft and non-sticky texture with clarity, a pandan-like aroma, and excellent adhesion and spreadability. It contains proteins and antioxidants that help wound healing. The lyophilized-Sec gel contained TIMP-2, EGF, bFGF, IL-6, and IL-4 as well as stronger antioxidant properties compared to un-lyophilized-hWJMSCs-Sec gel, and showed promise as an effective remedy for wound healing. HIGHLIGHTS Assessment of the mechanism of action underlying the wound healing effects of the gel, such as its influence on cellular processes, growth factor release, and antioxidant activity. Investigation of the secretome combination with carbomer gel in providing a convenient application for wound treatment. Preservation of active ingredients in the secretome through lyophilization, ensuring stability and enabling extended storage duration. GRAPHICAL ABSTRACT